The negative prognostic impact of bone metastasis with a tumor mass (Clinics, 2015)
OBJECTIVE: Typically, bone metastasis causes osteolytic and osteoblastic lesions resulting from the interactions of tumor cells with osteoclasts and osteoblasts. In addition to these interactions, tumor tissues may grow inside bones and cause mass lesions. In the present study, we aimed to demonstrate the negative impact of a tumor mass in a large cohort of patients with bone metastatic cancer. METHODS: Data from 335 patients with bone metastases were retrospectively reviewed. For the analysis, all patients were divided into three subgroups with respect to the type of bone metastasis: osteolytic, osteoblastic, or mixed. The patients were subsequently categorized as having bone metastasis with or without a tumor mass, and statistically significant differences in median survival and 2-year overall survival were observed between these patients (the median survival and 2-year overall survival were respectively 3 months and 16% in patients with a tumor mass and 11 months and 26% in patients without a tumor mass; p